Penggunaan Abreviasi, Singkatan, dan Akronim dalam media WhatsApp di SMK Bina Sejahtera 1 Kota Bogor - Deasy Supartini; Siti Solihah (Universitas 45 Surabaya, 2022)
This study aims to describe the form of abbreviations and patterns of word fragments used by Indonesian millennial teenagers in WhatsApp media. For example, the use of abbreviations and acronyms in communication. This fact is one of the novelties in the use of language. However, if the novelty is not limited in its use, it will be fatal, namely the loss of language function. The method used in this study is a content analysis method that examines a text or other communication media, one of which is WhatsApp media. According to Fraenkel and Wallen the definition of content analysis is content analysis, which is a technique that allows researchers to study human behavior indirectly, through the analysis of their communication. This study describes the formation and typology of abbreviations contained in WhatsApp media at SMK Bina Sejahtera 1 Bogor City. This study used descriptive qualitative method. The data in this study are all speech abbreviations and acronyms made by students of SMK Bina Sejahtera 1 Bogor City both orally and in writing. The data sources in this study were students of SMK Bina Sejahtera 1 Bogor City and the social media network WhatsApp. The factors that cause the use of abbreviations and acronyms among students of SMK Bina Sejahtera 1 Bogor City both in oral and written form, namely in oral form, the factor that causes is because they want to be considered a cool group because they have followed the times, dashing , slang, and not out of date, while in short writing, simple, saving words, words, and not wanting to follow EYD. WhatsApp is an internet-based application that allows each user to share various kinds of content according to the supporting features. The features contained in WhatsApp are gallery to add photos, contacts to insert contacts, camera to take pictures, audio to send voice messages, maps to send various map coordinates, even documents to insert files in the form of documents. All these files can be instantly sent through the free application. These various features certainly add to the ease and convenience of communicating through online media.